Soil carbon status after vegetation restoration in South West Iceland - Harrington Nyirenda (Heliyon, 2020)
Reclamation of degraded land using revegetation is one way of sequestering carbon into the soil. In this study an assessment was done to estimate the status of soil carbon amounts after revegetation with trees and grass in South West Iceland (Hafnarmelar). Natural woodland and eroded plots were part of the assessed plots as controls making four treatments. Soil samples were analysed for bulk density, carbon content and soil texture. Total % carbon (C) was analysed using vario MAX CN analyser (measured % C) and Loss on Ignition (calculated % C). The results showed that natural woodland had higher (9.32%) C than the tree treatment (4.91%), and both had significantly higher C than the grass (1.12%) and the eroded (0.76%) treatments (p < 0.0001). The amount of C in the grass and the eroded treatments were not statistically different (p > 0.0566). Notably, the grass treatment had carbon below the minimum expected level of 1.5% in Icelandic Andosol under vegetation. The natural woodland and the tree treatment had fine soil texture than the grass and eroded plots. Results suggest that where land has been properly restored or kept in natural condition, soil properties improve significantly especially when trees are part of the restored vegetation. The natural woodland had possibly not lost the old carbon-rich soil, as was the case with the tree, grass and eroded plots hence more time for development of various soil properties. Moreover, more litter deposits in natural woodlands and partly in the tree treatments might have contributed to higher carbon than in the grass and eroded treatments. Furthermore clay content variations (natural woodlands and the tree treatments had finer soil texture) might also be responsible for C limitations in the grass and the eroded treatments. Therefore, more restoration efforts are encouraged. The results also showed that LOI is a good method for C estimation but not very accurate estimator of soil organic carbon unless equations are developed with respect to known carbon content of ...